(untitled) (Bulletin KNOB, 2001)
The article deals with the reconstruction of the meeting hall of the ’heren XVII’ of the Dutch East India Company in the Amsterdam East Indian House as a representative reception room of the Amsterdam University. The essence of the article is the moral question to what extent a reconstruction does justice to the history and historical values of a historically important building. The question is further worked out on the basis of the questions whether the reconstruction itself is to be called successful and whether the chosen location of the hall is historically correct. The authors take the view that a proof of professional skill was achieved in the hall, but that in parts of it the quality of the work was less good. In two cases, not clearly distinguishable to the layman, interior components were applied for embellishment, which have no historical basis. According to the authors it is most likely that the location of the hall was at the front side on the upper floor and far less likely at the rear side on the ground floor, the place of the reconstruction. The most important proof is the place of the chimneys in historical prints. In 1811 these chimneys were pulled down for the purpose of a new heating plan. Not one single clue has been found for localising the hall on the ground floor at the rear. The article is a plea for elaborate building-historical research prior to any reconstruction and recommends operating with a certain caution in the event of lack of sufficient remains.